PENAMPILAN KARAKTER AGRONOMI DAN KOMPONEN HASIL EMPAT VARIETAS SORGUM MANIS (Sorghum bicolor L.) PADA BERBAGAI JARAK TANAM - Erwin Djamaluddin; Aminah Aminah; Amin Nur (Percetakan Umi Toaha Makassar, 2023)
High productivity of sweet sorghum can be achieved by applying optimal cultivation technology, including the use of high-yielding varieties. Differences in sorghum varieties will refer to genetic factors in each sorghum variety. Increasing sorghum production and land use efficiency, it can be done by adjusting the spacing to obtain the ideal spacing. This study aims to determine and analyze the effect of variety and spacing on the appearance of agronomic characters and yield components of sorghum. This study was arranged based on a two-factor Randomized Block Design (RAK), as the first factor was four varieties of sorghum (V), namely Super 1 (V1), Super 2 (V2), Bioguma 2 Agritan (V3) and Numbu (V3) varieties. V4), the second factor was the spacing (J) with three treatment levels, namely 75 cm × 15 cm (J1), 75 cm × 20 cm (J2), and 75 cm × 25 cm (J3) so that 12 treatment combinations were obtained and repeated as many as 3 times. Each variety consists of 4 rows that are placed randomly. The results showed that the Bioguma 2 Agritan variety produced the appearance of agronomic characters with the highest plant average (293.82 cm), the highest number of leaves (13.59 strands), the highest number of internodes (13.68 books), and yield components in the form of an average the fastest flowering age (63.89 days), the fastest harvest age (103.11 days), the longest panicle (26.94 cm), the heaviest seed weight per panicle (81.58 g), the heaviest 1000 seed weight (31.33 g), highest brix content (18.21%) and highest production (2.24 kg plot-1 or 3.73 ton hectare-1). While the Super 2 variety produced an average stem with the widest diameter (21.80 mm). There is no effect of spacing on agronomic characters and yield components and there is no interaction effect between varieties and spacing on agronomic characters and yield components.